Parallel evolution of highly conserved plastid genome architecture in red seaweeds and seed plants. Issue 1 (December 2016) - Lee, JunMo; Cho, Chung; Park, Seung; Choi, Ji; Song, Hyun; West, John; Bhattacharya, Debashish; Yoon, Hwan
Abstract Background The red algae (Rhodophyta) diverged from the green algae and plants (Viridiplantae) over one billion years ago within the kingdom Archaeplastida. These photosynthetic lineages provide an ideal model to study plastid genome reduction in deep time. To this end, we assembled a large dataset of the plastid genomes that were available, including 48 from the red algae (17 complete and three partial genomes produced for this analysis) to elucidate the evolutionary history of these organelles. Results We found extreme conservation of plastid genome architecture in the major lineages of the multicellular Florideophyceae red algae. Only three minor structural types were detected in this group, which are explained by recombination events of the duplicated rDNA operons. A similar high level of structural conservation (although with different gene content) was found in seed plants. Three major plastid genome architectures were identified in representatives of 46 orders of angiosperms and three orders of gymnosperms. Conclusions Our results provide a comprehensive account of plastid gene loss and rearrangement events involving genome architecture within Archaeplastida and lead to one over-arching conclusion: from an ancestral pool of highly rearranged plastid genomes in red and green algae, the aquatic (Florideophyceae) and terrestrial (seed plants) multicellular lineages display high conservation in plastid genome architecture. This phenomenon correlates with, and could be explained by, the independent and widely divergent (separated by >400 million years) origins of complex sexual cycles and reproductive structures that led to the rapid diversification of these lineages.